Number of Brunner’s Glands in Different Parts of the Duodenum in Bengalis of Bangladeshi Population - Sayeed, Sharmina; Ara, Shamim (Bangladesh Journal of Anatomy, 2016)
Context: The existence of Brunner’s glands in the duodenal submucosa is uncontestable, but their exact numerical distribution along the full extent of the duodenal wall has not been reported in Bangladeshi Bengalis. To determine the numerical distribution of the Brunner’s glands along different parts of the duodenum in Bangladeshi Bengalis, a cross-sectional analytical type of study was carried out in the department of Anatomy, Dhaka Medical College, from July 2010 to June 2011. Materials & Methods: The study material consist of histological slides of 17 post mortem cadaveric duodenum of 20 to 59 years of age. The study samples were divided into four age groups: Group A (20-29 years), Group B (30-39 years), Group C (40-49 years) and Group D (50-59 years). Histological study was carried out on 5 study samples from each of Group A, B and C and 2 study samples from group D. One slide was prepared from each part of the duodenum: first, second, third and fourth. These were stained with hematoxylin-eosin stain. Three microscopic fields, each representative of one-third of a slide were examined from each slide. The number of Brunner’s Glands per field was counted; the mean number for each age group in each duodenal part was calculated. Result: The mean (± SD) number of the Brunner’s glands in first part of the duodenum per square millimeter was 61.10 (± 12.68), 53.00 (± 6.04), 58.13 (± 8.90) and 40.25 (± 7.42) for Groups A, B, C and D respectively. In the second part, it was 37.70 (± 9.22), 33.30 (± 6.06), 35.13 (± 2.10), 27.50 (± 4.24) respectively. In the third part, the number of the Brunner’s gland per square millimeter was 14.10 (± 14.54), 9.70 (± 9.14), 6.38 (± 5.12) and 5.25 (± 7.42) respectively and in the fourth part, it was 0.50 (± 1.12), for Group A. In the other age groups, there were no Brunner’s gland in this part of the duodenum. Conclusion: The number of Brunner’s gland was found maximum in the first part of the duodenum for all age groups and decreased in the second and third part of the duodenum and was absent in the fourth part of the duodenum. However, further studies to standardise this finding are recommended. Bangladesh Journal of Anatomy January 2016, Vol. 14, No. 1, pp. 5-8